(3efHY GdMjGI aj MLjI bhd GdeLJgO ef GdCehGJs - (3fYeI Gddg Hf YHO Gddg Hf eMeO Hf MSjf GdMSjfj GdLRGFQj , J (B1112 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdYHO fYeI Gddg GdMSjfi GdLRGFQi hLYd eG jCJi s
(3BNQgG (B:s
(3Cf jJaVd YdjfG HJYLjd XghQ UGMH GdOGQ Ydjg hYdi BHGFg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B39 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B110s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B566s
Keywords: (3abg GdePGgH GdCNQis